2003
DOI: 10.1117/12.510046
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous temperature and strain sensing for cryogenic applications using dual-wavelength fiber Bragg gratings

Abstract: A new technique has been developed for sensing both temperature and strain simultaneously by using dual-wavelength fiber-optic Bragg gratings. Two Bragg gratings with different wavelengths were inscribed at the same location in an optical fiber to form a sensor. By measuring the wavelength shifts that resulted from the fiber being subjected to different temperatures and strains, the wavelength-dependent thermo-optic coefficients and photoelastic coefficients of the fiber were determined. This enables the simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…While there have been some research into the characterization of FBG sensors at cryogenic temperatures [1][2][3][4]7], few have studied both strain and temperature dependence. James et al [1] reported that the strain response of a FBG was temperature-independent between 2.2 and 280 K. To further identify the relationship between strain sensitivity and temperature, we investigate the response of FBGs from 123K to 273K, up to a maximum applied strain of 5000 / m m µ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been some research into the characterization of FBG sensors at cryogenic temperatures [1][2][3][4]7], few have studied both strain and temperature dependence. James et al [1] reported that the strain response of a FBG was temperature-independent between 2.2 and 280 K. To further identify the relationship between strain sensitivity and temperature, we investigate the response of FBGs from 123K to 273K, up to a maximum applied strain of 5000 / m m µ .…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing requirement to monitor the health and usage of structures designed to operate at cryogenic environments [1][2][3][4], for example, liquid hydrogen fuel tanks employed in aerospace vehicles, storage or transport vessels for cryogens, superconducting magnet support structures and particle physics experiments. The resistive foil strain gauge (RFSG) has remained the device most commonly used for measuring the strain on cryogenic structures over the past four decades.…”
Section: Introductionmentioning
confidence: 99%
“…The novel development of a wavelength swept laser source with speeds over 10 kHz is strongly expected to broaden the range of applications of the FBG sensor systems, such as monitoring the real-time strain of the high-speed dynamic fluidic sloshing pressure in a liquefied natural gas (LNG) carrier ship [13][14][15][16][17]. Since electric-type sensors do not work properly in a cryogenic temperature environment (< -160 o C), FBG sensors have been expected to become an ideal dielectric device for massive LNG carrier ships but their maximum interrogating speed has been limited to the kHz regime [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed an ultra-fast 31.3 kHz FBG sensor system that operates in the 1.5 ㎛ wavelength regions using Fourier domain mode-locked (FDML) swept laser technology. Given the rapidly increasing global demand for oil and natural gas, this novel advancement in ultra-fast interrogation may be useful for the real-time strain monitoring in the hazardous cargo containment of LNG tankers, in addition to the ideal nature of explosive-free, multi-point telemetry and low-temperature performance of the FBG sensor [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such disadvantages, fiber Bragg gratings (FBG) based flow meters are being preferred over the conventional ones [1,2]. FBG sensors are considered to be viable candidates for such applications due to their miniature size, high sensitivity, corrosion resistance, wide operational range, multiplexing capabilities and immunity to electrical and magnetic fields [3,4]. As the current study is focused on cryogenic flow, the sensors have to withstand extremely low temperatures.…”
mentioning
confidence: 99%